Preliminary evaluation of antioxidant and antimicrobial activities of Luffa Operculata (L.) Cong. extracts (Acta Scientiarum. Health Sciences, 2020)
Luffa operculata is a medicinal plant widely used in the treatment of rhinosinusitis in Brazil. The aim of this work was to carry out a preliminary analysis of the antioxidant and antimicrobial profile of Luffa operculata extracts. The antioxidant activity of the commercial solution, hydroalcoholic extract, infusion and ethanolic extract obtained from the commercialized fruit were evaluated for 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS•+) and 2,2-Diphenyl-1-picrylhydrazyl (DPPH•) radicals. The antimicrobial activity was determined by minimum inhibitory concentration against the pathogens Staphylococcus aureus, Escherichia coli and Candida albicans. It was shown that the hydroalcoholic extract exhibited the highest antioxidant and antimicrobial activity when compared to the aqueous and ethanolic extracts by the methods employed on this work. Thus, the extracts of Luffa operculata are a good source of active principles with pharmacological activity.